Exploring the acceptability of using low-friction bedding for patients with burns: Qualitative results from the SILKIE study. Issue 5 (August 2018) - Whale, K.; Ingram, J.C.; George, S.; Spickett-Jones, F.; Sack, A.; Young, A.E.
Highlights: The use of low-friction bedding is acceptable to patients undergoing a skin graft following a burn injury. The non-porous nature of low-friction sheets presents a challenge in dealing with soiling and exudate. The need for more frequent sheet changes because of leaking and soiling leads to increased staff work time. Low-friction underpads with polyolefin support, gowns, or low-friction outer covers are potential alternatives to bedding. Abstract: Background: Skin grafts following deep burns are needed to ensure healing. Grafts that fail and require re-grafting cause significant distress to patients and additional costs for the NHS. Shearing, which leads to graft loss, may be reduced through the use of low-friction bedding. A feasibility study was conducted to assess proof of concept for the use of low-friction bedding for patients with burns. Patient, parent and staff views on the acceptability of this material were explored through semi-structured interviews. Method: Patient views were gathered through telephone interviews (n = 17; 11 adult patients and 6 parents of child patients). One patient completed the questionnaire in written form because of hearing difficulties. Staff views were gathered at two time points: at the start of the study through open-ended questionnaires (n = 20) and at the end of the study through focus group (n = 12) and telephone interviews (n = 3). Data were analysed using framework analysis. Results: Three themes were identified describing both patient and staff views of the sheets: Slippery feel of the sheets; leaking wounds and sheet changes; and movement and friction. Overall patients' views of the sheets were positive; they were comfortable to use the sheets and experienced reduced pain and itching. However, issues related to the slipperiness were highlighted. Staff views were largely negative because of difficulty in use, lack of absorbency, and increased workload. Conclusion: The use of low-friction bedding is acceptable to patients undergoing a skin graft following a burn injury; however, problems related to sliding down the bed and soiling of sheets need addressing. Staff were supportive of the concept of low-friction bedding; however, they reported significant challenges in day-to-day use of sheets. Low-friction bedding presents a promising alternative to standard cotton sheets for patients with burns and those at risk of pressure sores; however, further work is needed to address current challenges in use.